Efektivitas supervisi akademik berkelanjutan untuk meningkatkan kompetensi guru dalam penyusunan alur tujuan pembelajaran dan modul ajar di MTsN 1 Kendal - Alfan, Ahmad (Journal of Smart Education and Learning, 2025)
This study examined the implementation of continuous academic supervision to improve teachers' competence in developing Learning Objectives Flow (ATP) and Teaching Modules at MTsN 1 Kendal. The research was motivated by the finding that only 60 percent of teachers had prepared ATP and Teaching Modules, and only 30 percent met the required quality standards. A school action research design was used in two cycles involving all teachers at MTsN 1 Kendal. Each cycle included planning, implementation, observation, and reflection stages. The supervision process focused on providing mentoring, offering feedback, and conducting follow-up evaluations. The results indicated a significant improvement in teachers' competence after the continuous academic supervision. The results indicated a significant improvement in teachers' competence after the implementation of continuous academic supervision, with the percentage of teachers preparing ATP and Teaching Modules increasing to 90 percent, and their quality reaching 80 percent according to the established criteria. Therefore, continuous academic supervision conducted systematically and reflectively proved effective in enhancing teachers' professional competence, ensuring the originality of instructional documents, and improving the overall quality of teaching and learning in MTs Negeri 1 Kendal.